Implications of miR-148a-3p/p35/PTEN signaling in tau hyperphosphorylation and autoregulatory feedforward of Akt/CREB in Alzheimer's disease - Li Zeng; Hailun Jiang; Ghulam Md Ashraf; Jianghong Liu; Linlin Wang; Kaiyue Zhao; Mimin Liu; Zhuorong Li; Rui Liu (Elsevier, 2022)
Existing studies have revealed that microRNAs (miRNAs) have a role in cognitive deficits in Alzheimer's disease (AD). However, the function and pathophysiological mechanism of deregulated miRNAs underlying AD pathology remain to be investigated. The present study aimed to clarify the role and mechanism of miR-148a-3p in AD. RNA sequencing, qRT-PCR, and western blot analysis were used to identify the aberrant expression and signaling of miR-148a-3p within cells, mice, and patients with AD. Molecular biology techniques involving luciferase reporter assays, gene overexpression and silencing, chromatin immunoprecipitation, and adeno-associated virus-based miRNA overexpression were used to explore the biological function and mechanisms of miR-148a-3p. Downregulation of miR-148a-3p was identified in AD. Upregulation of miR-148a-3p was found to protect neuronal cells against Aβ-associated tau hyperphosphorylation by directly targeting p35/CDK5 and PTEN/p38 mitogen-activated protein kinase (MAPK) pathways. A mutual regulatory link between miR-148a-3p and PTEN using a feedforward arrangement was confirmed via promotion of transcription and expression of miR-148a-3p by way of the PTEN/Akt/CREB pathway. Significantly, in vivo targeting of miR-148a-3p signaling ameliorated cognitive deficits by decreasing p35/PTEN-elicited tau hyperphosphorylation, accompanied by feedforward transduction of the PTEN/Akt/CREB pathway. In conclusion, the present study implicated the miR-148a-3p/p35/PTEN pathway as an essential contributor to tau hyperphosphorylation and feedforward regulation in AD.